Effects of Medications Used in ADHD on the Cardiovascular Risk: A Review of the Current Literature - Kępska, Julia; Kowalczyk , Wiktor; Olech , Weronika; Synakiewicz, Aneta; Lewińska, Natalia; Pociej, Aleksandra Iga; Drobashko , Arina; Murawska , Nikola; Wójcik, Kamil (Journal of Education, Health and Sport, 2026)
Background: Attention-deficit/hyperactivity disorder (ADHD) is a common neurodevelopmental disorder frequently treated with stimulant and non-stimulant medications. Due to the increasing use of ADHD pharmacotherapy, concerns regarding cardiovascular safety have become increasingly important. Aim: This review aimed to summarize current evidence regarding the cardiovascular effects of medications used in ADHD. Materials and Methods: A narrative review was conducted using PubMed, Scopus, and Web of Science databases. Studies published between 2015 and 2026 evaluating cardiovascular outcomes associated with ADHD medications were included. Results: Current evidence indicates that ADHD medications may cause modest increases in blood pressure and heart rate, mainly due to enhanced sympathetic nervous system activity. Stimulants demonstrated stronger hemodynamic effects, whereas α2-adrenergic agonists were associated with reductions in blood pressure and heart rate. Most studies did not demonstrate a substantial increase in serious cardiovascular events in the general ADHD population. However, higher cardiovascular risk may occur in patients with pre-existing cardiovascular disease, arrhythmias, or long-term cumulative medication exposure. Conclusions: ADHD medications are generally associated with mild and manageable cardiovascular effects in most patients. Nevertheless, individualized cardiovascular risk assessment and regular monitoring remain important, particularly in high-risk populations.